Phosphatidic acid production regulated by receptors with liganddependent tyrosine kinase activity - Fco. J. G. Muriana; V. Ruiz-Gutiérrez (Grasas y Aceites, 1995)
The present study deals with the most recent and important studies on the relationship between transmembrane receptors with ligand-dependent tyrosine kinase activity and cellular lipid metabolism, predominantly in generating phosphatidic acid (PA) as a lipid messenger. The signaling function of phosphatidylcholine hydrolysis and diacylglycerol (DG) phosphorylation by phospholipase D and diacylglycerol kinase, respectively, as different sources for PA is also described. PA may play a role in signal transduction as a putative first or second messenger, and acts to reduce levels of DG and to produce bis-PA by phospholipase D - mediated transphosphatidylation.